Overexpression of a disintegrin and metalloproteinase 21 is associated with motility, metastasis, and poor prognosis in hepatocellular carcinoma. Issue 1 (December 2017) - Honda, Hiroki; Takamura, Masaaki; Yamagiwa, Satoshi; Genda, Takuya; Horigome, Ryoko; Kimura, Naruhiro; Setsu, Toru; Tominaga, Kentaro; Kamimura, Hiroteru; Matsuda, Yasunobu; Wakai, Toshifumi; Aoyagi, Yutaka; et al.
Abstract Cell motility plays an important role in intrahepatic metastasis of hepatocellular carcinoma (HCC), and predicts poor prognosis in patients. The present study investigated the role of a disintegrin and metalloproteinases (ADAMs) in HCC, since these proteins are known to be associated with cell motility. We confirmed the expression of 12 ADAMs with putative metalloproteinase activity in HCC cells, and established a KYN-2 HCC cell line stably expressing short interfering RNA against ADAM21 to investigate the effect of ADAM21 deficiency on HCC cell motility and metastasisin vitro andin vivo . We also examined ADAM21 expression in a cohort of 119 HCC patients by immunohistochemistry. ADAM21 was overexpressed in KYN-2 cells, and its knockdown reduced invasion, migration, proliferation, and metastasis relative to controls. In clinical specimens, ADAM21 positivity was associated with vascular invasion, large tumor size, high histological grade, and lower overall and recurrence-free survival as compared to cases that were negative for ADAM21 expression. A multivariate analysis revealed that ADAM21 positivity was an independent risk factor for overall (P = 0.003) and recurrence-free (P = 0.001) survival. These results suggest that ADAM21 plays a role in HCC metastasis and can serve as a prognostic marker for disease progression.